Approach for analysis and modeling of reliability of network connectivity from the perspective of efficiency and its applicability - Simeonova, Tsvetelina (Yearbook Telecommunications, 2021)
Reliability analysis and assessment methods can be used at any stage of system or component design, including development, operation, and maintenance. Fault Tree-based models and reliability block diagram RBD (qualitative and quantitative) are typically used to provide reliability and readiness assessments for both the early and later stages of design, where system models are more -improved and have more detailed specifications compared to the models of the early stage of the system. On the other hand, models based on the Markov Chain are mainly used in the later design phase. The aim of the work is to define ways to use methods for modeling reliability, with a subsequent goal for analysis taking into account the effectiveness. An approach for modeling the end-to-end network connectivity with different reservations of the connection lines is considered. The results are illustrated by graphical ratios at different influencing parameters, for different reservation methods. A comparative analysis was made using different reservation methods. The practical applicability of the proposed approach and the performed analysis, incl. for training purposes.